2010
DOI: 10.5194/angeo-28-1993-2010
|View full text |Cite
|
Sign up to set email alerts
|

Fresnel scatter revisited – comparison of 50 MHz radar and radiosondes in the Arctic, the Tropics and Antarctica

Abstract: Abstract. High-resolution radiosondes and calibrated radars operating close to 50 MHz, are used to examine the relationship between the strength of radar scatter and refractive index gradient. Three radars are used, in Kiruna in Arctic Sweden, at Gadanki in southern India and at the Swedish/Finnish base Wasa/Aboa in Queen Maud Land, Antarctica. Calibration is accomplished using the daily variation of galactic noise measured at each site. Proportionality between radar scatter strength and the square of the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Each block consists of 12 kW power and feeds a separate 1/6th of the antenna array, so such dropouts also affect A e (for transmission). In order to correctly estimate η, allowing for major dropouts in P t and possible changes in L, we use the result found by Kirkwood et al (2010a) concerning radar-radiosonde comparisons in the upper troposphere/lower stratosphere (UTLS) region. For the UTLS region, Kirkwood et al (2010a) showed that Fresnel scatter, as quantified by the normalised power reflection coefficient ρ 2 / r, is proportional to M 2 , where M is the dry term of mean vertical gradient of generalized potential refractive index.…”
Section: Independent Calibrationmentioning
confidence: 99%
“…Each block consists of 12 kW power and feeds a separate 1/6th of the antenna array, so such dropouts also affect A e (for transmission). In order to correctly estimate η, allowing for major dropouts in P t and possible changes in L, we use the result found by Kirkwood et al (2010a) concerning radar-radiosonde comparisons in the upper troposphere/lower stratosphere (UTLS) region. For the UTLS region, Kirkwood et al (2010a) showed that Fresnel scatter, as quantified by the normalised power reflection coefficient ρ 2 / r, is proportional to M 2 , where M is the dry term of mean vertical gradient of generalized potential refractive index.…”
Section: Independent Calibrationmentioning
confidence: 99%
“…(4) for various values of aspect sensitivity for the actual ESRAD transmitted beam width. 6 rectangular antenna subarrays were used for reception (each 6 × 8 Yagi antennas, 4 × 6 before 2004), with mean beam width θ R of 6 • (9 • before 2004) as described in more detail by Kirkwood et al (2010). In Fig.…”
Section: Calculation Of Aspect Sensitivitymentioning
confidence: 99%
“…Moreover, isotropic (turbulent) and Fresnel scattering mechanisms lead to very different cross-sections (e.g. Kirkwood et al, 2010). Therefore in the cases of isotropic and aspectsensitive PMSE, estimation of their cross-sections using observations requires quite different calculations to account for radar characteristics (for a given echo power at the radar receiver, volume reflectivity of isotropic scattering depends on the antenna effective area, whereas Fresnel reflectivity depends on the square of that area).…”
Section: Introductionmentioning
confidence: 99%
“…However, soon after the development of ST radars, concurrent measurements of atmospheric parameters from balloons launched near radar sites have been made for interpreting the radar echoes, with some notable successes (e.g., Röttger and Larsen, 1990;Gage, 1990). In particular, a large number of studies have reported a close relationship between the echo power P v at vertical incidence (hereafter, P v will refer to the echo power corrected from the range attenuation effects by the product, i.e., P × z 2 , where P is the echo power and z is the altitude) and the square of the vertical gradient of the generalized potential refractive index M 2 (Ottersten, 1969) in clear-air conditions, calculated from balloon data at the vertical resolution of the radar measurements (e.g., Röttger, 1979;Röttger, 1983, 1985;Tsuda et al, 1988;Hocking and Mu, 1997;Hooper and Thomas, 1998;Low et al, 1998;Hooper et al, 2004;Vaughan et al, 1995;Luce et al, 2007;Kirkwood et al, 2010). But radiosonde measurements provide "instantaneous" values only along the path of the balloon, which tends to move as much as a few tens of kilometers or more away from the radar due to wind drift.…”
Section: Introductionmentioning
confidence: 99%